How to read a dress : a guide to changing fashion from the 16th to the 21st century - Edwards, Lydia (Bloomsbury Visual Arts, 2021)
"With lavish color images and commentary on the key features of every major dress style across five centuries, How to Read a Dress is the ultimate guide to how fashions change and the ideal tool for identifying historical styles"- Resumé vydavatel